Emergency Oral Anticoagulant Reversal: The Relative Efficacy of Infusions of Fresh Frozen Plasma and Clotting Factor Concentrate on Correction of the Coagulopathy - Makris, Mike; Greaves, Mike; Phillips, Wendy S; Kitchen, Steve; Rosendaal, Frits R; Preston, F Eric (Thrombosis and Haemostasis, 1997)
Haemorrhage, including intracranial bleeding, is a common, potentially lethal complication of warfarin therapy and rapid and complete reversal of anticoagulation may be life-saving. Fresh frozen plasma (FFP) and vitamin K are most frequently administered. Because of the variable content of vitamin K-dependent clotting factors in FFP, and the effects of dilution, the efficacy of this approach is open to doubt. We have therefore compared the effects of FFP and clotting factor concentrates on the INRs and clotting factor levels of orally anticoagulated subjects requiring rapid correction of their haemostatic defect. In many, the pre-treatment INR was considered to be dangerously above the target therapeutic range. In the 12 patients given FFP, the INR did not completely correct (range 1.6-3.8, mean 2.3) indicating an ongoing anticoagulated state in all. In contrast, the INR in 29 subjects given clotting factor concentrates was completely corrected in 28 (range 0.9-3.8, mean 1.3). Following treatment, marked differences were observed in clotting factor IX levels between the two groups. The median factor IX level was 19 u/dl (range 10-63) following FFP infusion and 68.5 u/dl (range 31-111) following concentrate. In FFP treated patients, poorer responses were also observed for each of the other vitamin K-depen- dent clotting factors but these were less marked than for factor IX, which was present in low concentrations in some batches of FFP. Thus, haemostatically effective levels of factor IX cannot be achieved, in most instances, by the conventional use of FFP in patients requiring reversal of their anticoagulant therapy. Clotting factor concentrates are the only effective option where complete and immediate correction of the coagulation defect is indicated in orally anticoagulated patients with life or limb-threatening haemorrhage.